Optimization of focusing SAW propagation in piezoelectric medium for microfluidic applications - Abd Aziz, Norazreen; Bais, Badariah; Buyong, Muhamad Ramdzan; Majlis, Yeop Burhanuddin; Nordin, Anis Nurashikin (2015)
In this study, a 2D axisymmetric finite element model of annular surface acoustic wave (A-SAW) resonator to evaluate the SAW propagation was modeled and its focusing properties on lithium niobate substrate was optimized. The analysis concept is based on utilization of patterned annular interdigital electrodes on piezoelectric substrate’s surface to generate surface acoustic waves with high intensity in a confined localized area.From the simulation results, it can be observed that acoustic amplitude field, displacement contours and waves propagation direction are significantly influenced by the geometric parameters of the device. Increasing number of finger pairs of annular electrodes produces high displacement amplitude meanwhile devices with smaller electrodes’ gap of 25 μm induced steeper focusing gradient compared to devices with 50 μm electrodes’ gap. Acoustic waves from device with large inner diameter of 500 μm require more time to be focused at the center of the device. From the analysis, it can be concluded that small diffraction limited acoustic spot at the center of A-SAW device is suitable for microfluidics application that requires detection or manipulation of localized variations.